Analysis of the Use of Frame Construction and Modular Additions in City Centre - Milwicz, Roman; Milwicz, Natalia; Dubas, Sebastian (IOP conference series. Materials Science and Engineering, 2017)
The living urban fabric can be characterized by the continuous introduction of changes and additions. The city centre is subject to specific restrictions due to the conservation protection and high demand on aesthetics aspect, thermal insulation, construction cost and the ratio of usable area of the building area. This article presents a comparative analysis of traditional construction with light frame and modular construction for the above-mentioned issues. Timber frame structure technology was suggested as effective, economic and innovative solutions for modular additions on buildings in city centres.